SYNTHESIS, ELECTROCHEMISTRY AND COMPLEXATION STUDIES OF NEW REDOX ACTIVE BISFERROCENE ACYCLIC AND MACROCYCLIC THIOETHERS - Beer, P; Nation, J; Harman, M; Hursthouse, M (1992)
The syntheses and electrochemical studies of new bisferrocene acyclic and macrocyclic ligands are described. Preliminary coordination investigations with palladium(II) and rhodium(I) transition metals produced, in most cases, polymeric complex species. Mono- and bimetallic copper(II) complexes of two macrocyclic ligands and a nickel(II) complex of an acyclic analogue have been isolated and characterized. © 1992.